Screening and identification of grain sorghum germplasm for salt tolerance at seedling stage - Wang, Yu; Li, Dongyang; Liu, Chunjuan; Shi, Xiaolong; Huang, Yan; Liu, Chang; Zhou, Yufei (Frontiers in Plant Science, 2025)
IntroductionSorghum is characterized by its salt tolerance, and holds great potential for cultivation in saline-alkali soils.MethodsThis study aimed to comprehensively evaluate the salt tolerance of grain sorghum germplasm. The experiment was conducted with 188 grain sorghum germplasm accessions selected to investigate the morphological and physiological index of seedlings under 150 mM NaCl stress. A comprehensive salt tolerance evaluation system was constructed using six indicators: shoot length (SL), root length (RL), shoot fresh weight (SFW), root fresh weight (RFW), shoot dry weight (SDW), and root dry weight (RDW). The salt tolerance level of the 188 accessions was evaluated using methods including the salt tolerant index (SI), the Spearman correlation analysis, the membership function analysis, the principal component analysis (PCA), and the cluster analysis.ResultsThe results were classified into five categories: highly salt tolerant, salt-tolerant, moderate, salt-sensitive, and highly salt-sensitive. The comprehensive evaluation revealed significant variability in salt tolerance among the sorghum germplasm, with an overall trend of normal distribution. The loadings of shoot growth parameters (SFW and SDW) were relatively high, explaining most of the information in the first principal component. Therefore, shoot growth status can be used as an important standard for evaluating salt tolerance in sorghum. Among the accessions, LCS177 and LCS234 exhibited extremely high salt tolerance, while LCS140 and LCS181 showed highly sensitive of salt tolerance. Further analysis of the physiological characteristics of salt tolerance in the selected extreme accessions revealed that under salt stress, the increases in proline, soluble protein, and soluble sugar contents were significantly higher in the salt-tolerant accessions LCS177 and LCS234 than in the salt-sensitive accessions LCS140 and LCS181. In terms of oxidative stress, the activities of SOD, POD, and CAT were significantly higher in the salt-tolerant accessions LCS177 and LCS234, while the content of MDA was significantly lower in salt-tolerant accessions compared to that of in salt-sensitive accessions LCS140 and LCS181.DiscussionThe results of this study provide a material basis for the improvement of salt tolerance in sorghum germplasm resources and for the breeding of salt-tolerant sorghum varieties.